Comparative Analysis of Indonesia Gross Split PSC with Fiscal Terms of Several Southeast Asian Countries - Saptianta Aribawa Sabaris; Asri Nugrahanti; Dwi Atty Mardiana (Journal of Earth Energy Science, Engineering, and Technology, 2020)
The implementation of the Gross Split PSC in the upstream oil and gas industry in Indonesia has been running since 2017 with the hope of being able to accelerate the decision-making process and increase attractiveness for oil and gas investors. This study is to analyze the implementation of Indonesia Gross Split PSC compared to other fiscal terms in Southeast Asia region from an economics perspective. The comparisons reviewed are between Indonesia Gross Split PSC and the following fiscal terms: Indonesia Cost Recovery PSC, Malaysia R/C PSC, Thailand Concession, and Vietnam PSC. Fields used as input for analysis are producing oil fields with small-scale recoverable reserves according to RF-2005 / SPE, namely Block X (early production fields) and Block Y (terminated fields). From economics calculations and comparisons, sensitivity and profitability characteristics, specifically applied to the field conditions under review, it is concluded that Indonesia Gross Split PSC has improved economics indicators compared to Indonesia Cost Recovery PSC so that Indonesia Gross Split PSC has an economics level indicator that is better than PSC Indonesia Cost Recovery when compared to Malaysian R/C PSC, Thailand Concession and Vietnam PSC.